Índice de masa corporal, hábitos alimenticios y actividad física en los docentes de la Unidad Educativa Saraguro, Saraguro - Ávila Jiménez, Carmen Vanessa (2024)
Body mass index (BMI) is one of the anthropometric measures used to classify weight groups. Eating habits (EH) involve consistent choices by the individual regarding selection, quantity, and frequency of food consumed during the day. Physical activity (PA) is any bodily movement that involves energy expenditure. The purpose of the research was to classify the body mass index, to know the eating habits and physical activity and to establish the relationship between these variables in the teachers of the Unidad Educativa Saraguro, Saraguro according to sex and age, in the school year September 2021 - July 2022. It was configured as a quantitative approach and cross-sectional cohort research, formed by 68 teachers, to whom the body mass index was measured based on the World Health Organization 2010 classification (BMI), the Mediterranean diet adherence screening (CADM) and the international physical activity questionnaire (IPAQ) were applied. We obtained a distribution according to sex and age of 58.82% (n=40) corresponding to the age group 41 to 64 years of men and women. Preobesity/overweight was evidenced in 90.48% (n=30), of which 40.48% (n=17) were women and 50.00% (n=13) men; 57.50% (n=18) class I obesity, 19.04% (n=8) women and 38.46% (n=10) men. In addition, 11.90% (n=5) and 4.76% (n=2) female teachers showed class II and III obesity, respectively. When applying the (CADM) 26.48% (n=18) showed low, 52.94% (n=36) medium and 20.58% (n=14) high adherence and with (IPAQ), low physical activity was in 55.88% (n=38), moderate in 25.00% (n=17) and high 19.11% (n=13) in both sexes and mature adults. There was statistical correspondence between high adherence to the Mediterranean diet and high physical activity